2022
DOI: 10.1111/jerd.12924
|View full text |Cite
|
Sign up to set email alerts
|

Impact of cleansing protocols to remove endodontic sealer residues on the adhesive interface: Bonding with universal adhesive systems

Abstract: Objective: The aim of this study was to evaluate the effectiveness of cleansing protocols to remove sealer residues using different cleaning strategies and the effect of bond strength of two universal adhesives to dentin impregnated with epoxy resinbased sealer.Materials and Methods: Fifty bovine dentin specimens were impregnated with epoxy resin-based sealer containing calcium hydroxide (Sealer Plus) and submitted to cleansing protocols (n = 10): negative control (NC), positive control (PC), 95% ethanol (ET),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 29 publications
0
4
0
1
Order By: Relevance
“…However, 95% ethanol showed the lowest destructive effect on dentin microhardness and the Ca/P ratio. A previous study 14 reported that amyl acetate provided better cleaning than ethanol and did not affect the micro‐shear bond strength. Hypothetically, the combination of both solutions would be ideal.…”
Section: Discussionmentioning
confidence: 89%
See 3 more Smart Citations
“…However, 95% ethanol showed the lowest destructive effect on dentin microhardness and the Ca/P ratio. A previous study 14 reported that amyl acetate provided better cleaning than ethanol and did not affect the micro‐shear bond strength. Hypothetically, the combination of both solutions would be ideal.…”
Section: Discussionmentioning
confidence: 89%
“…However, 95% ethanol showed the lowest destructive effect on dentin microhardness and the Ca/P ratio. A previous study 14 of both solutions would be ideal. However, when amyl acetate and ethanol are mixed in a 1:1 ratio (E2), a significant persistence of residues was observed (Figures 1 and 2), probably because 95% ethanol has a portion of water that lower the miscibility with nonpolar substances presented in epoxy resin-based sealers, such as bisphenol A and B.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…resíduos do cimento endodôntico à base de resina epóxi com xilol, independentemente da sua composição química, proporcionou maior valor de resistência de união na interface de adesão com a dentina da coroa dental, quando utilizado o adesivo universal (SBU) na estratégia condiciona-elava. Portanto a hipótese nula foi rejeitada.4.1 DA METODOLOGIA UTILIZADAA avaliação da resistência de união entre o substrato dentinário e os sistemas adesivos por meio do teste de microcisalhamento é consagrada na literatura e utilizado em estudos que analisam os efeitos dos protocolos de remoção de resíduos de cimento endodôntico sobre a adesão dos compostos resinosos na dentina modificada endodonticamente(MANZOLI, 2022;ZANIBONI, 2022).O estudo foi realizado na face vestibular da coroa dental, devido à necessidade dos corpos de prova de resina composta estarem fixados em uma superfície plana e alinhados com o plano de tracionamento da célula de carga da máquina de ensaio eletromecânica(ESCALANTE-OTÁROLA, 2018). Com isto há a inviabilização de realizar o teste na dentina da câmara pulpar, que é côncava, mas devido a orientação dos túbulos dentinários no terço médio da coroa dental ser similar, tanto na face da câmara pulpar como próxima à junção amelocementária, a realização do estudo por planificação da face vestibular da coroa dental é viável(ZANIBONI, 2022).O cálculo amostral foi realizado a partir de um estudo piloto com 3 espécimes de cada grupo em análise, com 4 corpos de prova em cada espécime, totalizando 12 resultados de resistência de união no grupo analisado.A partir destes resultados, foi possível obter a média aritmética e o desvio padrão incidente em cada grupo, sendo possível realizar o tamanho da amostra na comparação da média de 4 grupos independentes, aplicados na análise de variância a 2 critérios e também fundamentada em estudos prévios (ESCALANTE-OTÁROLA, 2018; ZANIBONI, 2022).4.2 RESISTÊNCIA DE UNIÃO A remoção dos resíduos do cimento endodôntico à base de resina epóxi com etanol demonstrou os menores valores de resistência de união em relação aos grupos em que foi utilizado o xilol.…”
unclassified